An Indirect Inguinal Hernia Repair after Nitya Virechana a Case Report - B. Patel, Dr. Neelkumar; Kumar Sharma, Dr. Rajesh; Desai, Dr. Hardik (Asian Journal of Pharmaceutical Research and Development, 2024)
Over time, an inguinal hernia may develop due to increased pressure on the walls of the abdominal muscles from activities such as straining, prolonged coughing, being overweight, or lifting heavy weights. Acharya Sushruta referred to inguinal hernia as Antravridhhi[1]. This condition may be associated with symptoms such as dragging pain and discomfort. Paresthesia may occur in some patients due to compression or irritation of the inguinal nerves by the hernia. An indirect inguinal hernia which does not extend to the scrotal sac should be managed as vata vridhhi[2]. In describing the operative management of vata vridhhi, Acharya Sushruta recommended certain therapeutic procedures as a purvakarma of Vatavridhhi chikitsa. The patient undergo Nityavirechana karma with Eranda taila and Milk for 7 days, followed by hernioplasty on the 8th day. Tension-free mesh hernia repair has become the predominant method for treating inguinal hernias.